Profile of Remimazolam in Anesthesiology: A Narrative Review of Clinical Research Progress - Wang M; Zhao X; Yin P; Bao X; Tang H; Kang X (Dove Medical Press, 2022)
Mi Wang,1,* Xian Zhao,2,* Pengfei Yin,1 Xiuxia Bao,1 Hongli Tang,3 Xianhui Kang1 1Department of Anesthesiology, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People's Republic of China; 2Department of Anesthesiology, Shulan (Hangzhou) Hospital Affiliated to Zhejiang Shuren University Shulan International Medical College, Hangzhou, People's Republic of China; 3Department of Anesthesiology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Xianhui Kang, Department of Anesthesiology, The First Affiliated Hospital, Zhejiang University School of Medicine, No. 79 Qingchun Road, Hangzhou, Zhejiang, People's Republic of China, Tel +86-0571-87236169, Fax +86-21-57643271, Email kxhui66@zju.edu.cn Hongli Tang, Department of Anaesthesiology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People's Republic of China, Tel +86-577-87236169, Fax +86-21-57643371, Email tanghongliok@126.comAbstract: Remimazolam is a novel short-acting γ-aminobutyric acid (GABA) receptor agonist with typical characteristics of benzodiazepine sedative drugs, nonorgan-dependent metabolism, long-term infusion without accumulation, and no injection pain. It is quite different from the other current sedative drugs and has broad prospects for application. It has been established that the metabolites of remimazolam are inactive, and the interactions with other drugs are weak with slight cardiopulmonary suppressive effects, showing good effectiveness and safety. During the 2-year period that it has been on the market, remimazolam has been used in multiple clinical scenarios, such as the induction and maintenance of general anesthesia and sedation in outpatient minor procedures or examinations. However, it's use has also prompted widespread concern around the world. Therefore, given its short- and rapid-acting, controllable characteristics remimazolam deserves in-depth study in order for it to be used in fast-track surgery, comfort diagnosis and treatment. Notably, such agents might be of great significance, especially in elderly individuals, patients with critical diseases or patients with liver and kidney insufficiency. The current study reviews recent clinical studies (2015- 2022) on remimazolam and summarizes the characteristics of its applications. Specifically, the use of remimazolam in some specific populations are described. This study attempts to provide scientific support for the clinical application of this novel sedative drug in the field of anesthesia.Keywords: remimazolam, anesthesia, sedation, benzodiazepine, clinical